Filozoficzny problem czasu i przestrzeni u Leibniza - Woszczek, Marek (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
The problem of proper understanding of the space and time is one of the most enduring issues in the history of Western metaphysics. The article shows how Gottfried W. Leibniz approached them in the context of his broad relational stance in the metaphysics of nature and presents acute differences between this stance and the absolutivist-Newtonian view of space and time. Finally, some relevance of this controversy to the modern physics is pointed out.